BASIC REQUIREMENTS FOR THE USE OF NON-TRADITIONAL METHODS - Hakimov Sayibjon (International Multidisciplinary Journal for Research & Development, 2025)
In this article, at the current stage of development of the educational system, enrichment of practice with various personality-oriented technologies is considered as an important task, and one of them shows the basic requirements for teaching technology using non-traditional methods.